Regulation of the β-cell inflammasome and contribution to stress-induced cellular dysfunction and apoptosis - Ghiasi, Seyed Mojtaba; Dahllöf, Mattias Salling; Osmai, Yama; Osmai, Mirwais; Jakobsen, Kathrine Kronberg; Aivazidis, Alexander; Tyrberg, Björn; Perruzza, Lisa; Prause, Michala Cecilie Burstein; Christensen, Dan Ploug; Fog-Tonnesen, Morten; Lundh, Morten; et al. (Molecular and cellular endocrinology, 2018)
β-Cells may be a source of IL-1β that is produced as inactive pro-IL-1β and processed into biologically-active IL-1β by enzymatic cleavage mediated by the NLRP1-, NLRP3- and NLRC4-inflammasomes. Little is known about the β-cell inflammasomes. NLRP1-expression was upregulated in islet-cells from T2D-patients and by IL-1β+IFNγ in INS-1 cells in a histone-deacetylase dependent manner. NLRP3 was downregulated by cytokines in INS-1 cells. NLRC4 was barely expressed and not regulated by cytokines. High extracellular K+ reduced cytokine-induced apoptosis and NO production and restored cytokine-inhibited accumulated insulin-secretion. Basal inflammasome expression was JNK1-3 dependent. Knock-down of the ASC interaction domain common for NLRP1 and 3 improved insulin secretion and ameliorated IL-1β and/or glucolipotoxicity-induced cell death and reduced cytokine-induced NO-production. Broad inflammasome-inhibition, but not NLRP3-selective inhibition, protected against IL-1β-induced INS-1 cell-toxicity. We suggest that IL-1β causes β-cell toxicity in part by NLRP1 mediated caspase-1-activation and maturation of IL-1β leading to an autocrine potentiation loop. [Display omitted] •β-cell NLRP1 is upregulated by cytokines via lysine deacetylases.•JNK2/3 knockdown increases basal β-cell NLRP3 expression.•JNK1-3 knockdown reduces basal β-cell cell ASC expression.•ASC deficiency improved insulin secretion and β-cell viability.•Broad, but not NLRP3 selective inflammasome inhibition reduced β-cell death.